RHETORICAL ANALYSIS OF ENGLISH STUDENTS’ BUSINESS EXPRESSIONS:A RESEARCH PAPER - Supeno Supeno (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
In order to persuade, a speaker must analyze the speech situation and adapt his or her speech to it. In discussions about rhetoric, Aristotle is recognized as an expert in rhetoric who devoted more than a third of his Art of Rhetoric to study of the audience. Ever since, rhetoricians have taught that a speaker who would persuade others to believe and to act in a certain way must understand how the listeners feel, what they want, and what they need; the speaker must begin where the listeners are. A persuasive writing or speaking is often aimed at the heart or the stomach instead of the head. That is, some things or reasons are more acceptable to the readers or listeners’ feeling (in the stomach) than to their logic (in the head) . Instead of being logical only, therefore, a persuasive speaker needs to add some strategies to win the listeners’ assent. Discussed in terms of tripartite as the core theory of rhetoric, this paper is intended to analyse English students’ replies to their customers’ requests through WhatsApp business role-playing. The findings show that most of the students’ replies need to be rhetorically modified to make them more persuasive.